Environmental sustainability practices in the supply chain of hotels and the consumers’ perception - Alemão, Clarisse Patrício (2020)
Environmental sustainability is a central subject in the last years, due to the damage that human activity has been doing to the planet ecosystem. The concern is mostly based on consequences that it will have on future generations’ resources. The hotels’ industry is among the industries that generate more pollution and therefore affects environmental, social and economic sustainability. This dissertation evaluates the state of Portuguese hotels (on the cities of Porto, Lisbon and Algarve) regarding the presence of environmental sustainability practices on their supply chain, as well as the influence these practices may have on consumers. Through a survey two questionnaires were implemented: one to all the hotels (in Porto, Lisbon and Algarve) that were presented on the database of the national tourism association, and the other one to any consumer. From the 28 hotels, 18 have a low level of implementation of environmental sustainability practices (0 to 30 practices) and 10 are at a medium level (30 to 60). From the perspective of 178 consumers we found that more consumers consider social sustainability aspects when choosing a hotel than energy and environmental aspects. Furthermore, consumers are more willing to pay extra costs to have social sustainability features than energy and environmental sustainability features. This study gives insights to hotels and interested third parties such as tourism associations, sustainability related organizations, the government, and consumers.